Survival, treatment duration and costs of patients with prostate cancer treated with triptorelin in Italy: a study of administrative databases - Orazio Caffo; Gaetano Facchini; Luca Degli Esposti; Valentina Acciai; Giorgio Mauri; Paola Mazzanti; Giuseppe Fornarini (Global & Regional Health Technology Assessment)
Background: Several data support the efficacy/effectiveness, safety and favorable impact on quality of life of triptorelin treatment in patients with prostate cancer. However, little evidence is available concerning triptorelin use in the long term.